2016
DOI: 10.3892/or.2016.4701
|View full text |Cite
|
Sign up to set email alerts
|

miR-100 suppresses the proliferation and tumor growth of esophageal squamous cancer cells via targeting CXCR7

Abstract: MicroRNAs are highly conserved non-coding RNAs that regulate gene expression at the post-transcriptional level, and play pivotal roles in cancer development and progression. miR-100 has been reported to be significantly downregulated in a variety of cancers, including esophageal cancer. However, the role of miR-100 in human esophageal cancer has not been fully elucidated. We demonstrated that overexpression of miR-100 in esophageal cancer cells markedly inhibited cell proliferation, migration and invasion as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…17,18 Downregulation of miR-100 has been found in esophageal squamous cell carcinoma, non-small cell lung cancer, breast cancer, and so on. [20][21][22] On the other hand, upregulation of miR-100 is observed in small cell lung cancer, renal cell carcinoma, and pancreatic adenocarcinoma, and so on. [23][24][25] It has been also found that miR-100 play vital roles in various biological processes, such as cell proliferation, apoptosis, cell cycle, migration, differentiation, and angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Downregulation of miR-100 has been found in esophageal squamous cell carcinoma, non-small cell lung cancer, breast cancer, and so on. [20][21][22] On the other hand, upregulation of miR-100 is observed in small cell lung cancer, renal cell carcinoma, and pancreatic adenocarcinoma, and so on. [23][24][25] It has been also found that miR-100 play vital roles in various biological processes, such as cell proliferation, apoptosis, cell cycle, migration, differentiation, and angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, we deducted that miR-100 expression could suppress the cell proliferation in GC. Numerous miR-100 target genes have been identified in previous literatures (17,19,25,29,30). Using the bioinformatical tools, we found the 3'-UTR of CXCR7 has a putative binding site for miR-100 and the luciferase reporter assay confirmed CXCR7 is a direct target of miR-100.…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidences have found CXCR7 was highly expressed in a variety of human cancers, including GC (22)(23)(24). In particular, CXCR7 functions as a tumor promoter in esophageal squamous cancer and its expression can be regulated by miR-100 (25). However, whether or not miR-100 can regulate the expression of CXCR7 in GC requires more extensive investigations.…”
Section: Introductionmentioning
confidence: 99%
“…miR-100 was significantly down-regulated in esophageal cancer, and miR-100 overexpression in esophageal cancer cells significantly inhibited cell proliferation, migration and invasion and suppressed tumor growth via targeting CXCR7 [33]. miRNAs can also regulate sphere formation cell proliferation in esophageal cancer.…”
Section: Non-coding Rnas Molecular Functions In Esophageal Cancermentioning
confidence: 99%
“…miR-100 functions as a tumor suppressor in esophageal cancer, which could be potentially applied in treating esophageal cancer [33]. The miR-124/CDK4 axis was an important mechanism in regulating the radiation sensitivity of human esophageal cancer cells, and targeting CDK4 may improve the clinical efficacy of radiotherapy [48].…”
Section: Potential Biomarkers and Therapeutic Targets For Human Esophmentioning
confidence: 99%